PENENTUAN JENIS VEGETASI LOKAL UNTUK PERLINDUNGAN TEBING SUNGAI SIAK DENGAN DESAIN EKO - ENGINEERING TANPA TURAP - Euthalia Hanggari Sittadewi (Jurnal Teknologi Lingkungan, 2010)
Eco – engineering without civil’s construction design for the Siak riverside’s protection can be applied at the part of river has riverside’s weak damaged. The riverside’s protection system with eco – engineering without civil’s construction as the effort to make stronger the riverside with vegetation components. The used of local vegetation is the best choice for eco – engineering system. The identification of vegetation on the Siak river’s corridor as long as desa Merempan Hilir to choose the plants to make the eco – engineering withoutcivil construction’s design has been done. Some kind of plants have been choosen i.e :rumput teki (Cyperus rotundus), rumput kumpai (Hymenachne acutigluma) rumput akar wangi (Vetiveria zizanioides), karangkunan (Ipomea carnea), bambu kuning (Bambusa vulgaris), pandan (Pandanus, sp), bintaro (Cerbera manghas), rengas (Gluta renghas),kempas (Koompassia malaccensis), jawi – jawi (Ficus, sp) and meranti (Shorea, sp).Key words : desain eko – engineering tanpa turap, perlindungan tebing, tanaman lokal